Modulation of crude glycerol fermentation byClostridium pasteurianum DSM 525 towards theproduction of butanol - Gallardo, R. (2014)
High production yields and productivities are requisites for the development of an industrial butanol production process based on biodiesel-derived crude glycerol. However, impurities present in this substrate and/or the concentration of glycerol itself can affect the microbial metabolism. In this work, the effect of crude glycerol concentration on the production of butanol and 1,3-propanediol (1,3-PDO) by Clostridium pasteurianum DSM 525 is studied. Also, the effect of acetate and butyrate supplementation to the culture medium and the culture medium composition are evaluated. The results showed a marked effect of crude glycerol concentration on the product yield. The competitive nature of butanol and 1,3-PDO pathways has been evident, and a shift to the butanol pathway once using higher substrate concentrations (up to 35 g l 1) was clearly observed. Butyrate supplementation to the culture medium resulted in a 45% higher butanol titre, a lower production of 1,3-PDO and it decreased the fermentation time. Acetate supplementation also increased the butanol titre but the fermentation was longer. Even though glycerol consumption could not be increased over 32 g l 1, when the concentrations of NH4Cl and FeCl2 were simultaneously increased, the results obtained were similar to those observed when butyrate was supplemented to the culture medium; a 35% higher butanol yield at the expense of 1,3-PDO and a shorter fermentation. The results herein gathered suggest that there are other factors besides butanol inhibition and nutrient limitation that affect the glycerol consumption.